Preference for boys and length of birth intervals in Pakistan - Javed, Rashid; Mughal, Mazhar (Research in economics, 2020)
A potential manifestation of son preference prevalent in Asia is gender-specific birth-spacing. The time couples wait before moving on to subsequent pregnancy remains short as long as desired number of sons are not born, leading to higher demand on the mother's body and greater health risks for mother and child. In this study, we examine this phenomenon using three representative surveys of Pakistani households and duration model estimators. We find strong evidence for differential behavior at early parities. Women whose first or second children are sons have significantly longer subsequent birth intervals compared with women with no sons. Birth-spacing differs substantially by parity and number of children. The association seems to have undergone little significant change over the past two decades. Besides, the likelihood of risky births (i.e. those occuring less than 24 or 18 months from the previous birth) is higher among women without one or more sons.